2023
DOI: 10.1182/bloodadvances.2022008362
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of aberrant DNA and histone methylation synergistically suppresses tumor cell growth in ATL

Abstract: Adult T-cell leukemia/lymphoma (ATL) is a malignancy of mature CD4+ T cells caused by human T-cell lymphotropic virus type 1 (HTLV-1)-induced T-cell transformation. Following infection with HTLV-1, it takes several decades for HTLV-1 carriers to develop ATL. The prognosis of ATL remains poor despite several new agents are approved in the last few years. Recently, it has been noted that epigenetic abnormalities both DNA methylation and tri-methylation at histone H3Lys27 (H3K27me3) contribute to ATL leukemogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Our study suggests that simultaneously targeting repressive lysine methylation signaling at H3K27, particularly using the clinically applied EZH2i TAZ, represents a different approach to augmenting the transcriptional and therapeutic effects of DNMT inhibition. Recent studies have begun examining the combinatorial use of DNMTi and EZH2i, with reports of cooperative therapeutic benefit that include reduced xenografted tumor or cell line growth, antineoplastic action, increased T cell infiltration, resensitization to immunomodulatory drugs, reexpression of silenced TSGs, and activation of the viral mimicry response ( 10 , 35 , 37 40 , 79 ). Consistent with these findings, perturbing DNA methylation, genetically or as a consequence of chemotherapy and metabolic perturbation, renders cancer cells sensitive to EZH2 inhibition ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that simultaneously targeting repressive lysine methylation signaling at H3K27, particularly using the clinically applied EZH2i TAZ, represents a different approach to augmenting the transcriptional and therapeutic effects of DNMT inhibition. Recent studies have begun examining the combinatorial use of DNMTi and EZH2i, with reports of cooperative therapeutic benefit that include reduced xenografted tumor or cell line growth, antineoplastic action, increased T cell infiltration, resensitization to immunomodulatory drugs, reexpression of silenced TSGs, and activation of the viral mimicry response ( 10 , 35 , 37 40 , 79 ). Consistent with these findings, perturbing DNA methylation, genetically or as a consequence of chemotherapy and metabolic perturbation, renders cancer cells sensitive to EZH2 inhibition ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by recent studies showing that DNA hypomethylation, induced genetically or as a consequence of chemotherapeutic and metabolic perturbation, sensitizes cancer cells to EZH2 inhibition ( 34 36 ). Moreover, antineoplastic/therapeutic effects have also been shown for multiple cancer cell lines and tumor xenografts treated with DNMT and EZH2 inhibitors (EZH2is) ( 10 , 37 40 ). However, most clinical applications of EZH2is have focused on cancers addicted to PRC2 activity resulting from activating mutations in EZH2 or loss-of-function mutations in the SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex ( 41 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…3a). Recent research activities have indicated the contributions of epigenetic gene regulation to the oncogenesis of ATL; therefore, it would be possible that the ALKBH2 pre-mRNA expression was regulated in an epigenetic manner [36][37][38] . Regarding the observation in the ATL group, to our knowledge, there has been no report that HTLV-1 infection selectively inhibits host genomic pre-mRNA expression with no effect on mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, recent studies have shown that DNA hypomethylation, induced genetically or as a consequence of chemotherapeutic and metabolic perturbation, sensitizes cancer cells to EZH2 inhibition (53)(54)(55). Moreover, combination antineoplastic/therapeutic effects on multiple cancer cell lines and tumor xenografts have been reported following combined treatment with DNMT and EZH2 inhibitors (11,(56)(57)(58)(59). As clinical applications of EZH2 inhibition have primarily focused on cancers addicted to PRC2 activity resulting from activating mutations in EZH2 or loss of function mutations in subunits of the SWI/SNF chromatin remodeling complex (60)(61)(62)(63)(64), combining EZH2 inhibitors with DNMT inhibitors presents an opportunity to expand the utility of these epigenetic agents for cancer therapy.…”
Section: Introductionmentioning
confidence: 88%
“…Our study suggests simultaneously targeting repressive lysine methylation signaling at H3K27, particularly using the clinically applied EZH2 inhibitor TAZ, represents a different approach to augment the transcriptional and therapeutic effects of DNMT inhibition. Recent studies have begun examining the combinatorial use of DNMT and EZH2 inhibitors, with reports of cooperative therapeutic benefit that include reduced xenografted tumor or cell line growth, antineoplastic action, increased T-cell infiltration, re-sensitization to immunomodulatory drugs, re-expression of silenced TSGs, and activation of the viral mimicry response (11,54,(56)(57)(58)(59)109). Consistent with these findings, perturbing DNA methylation, genetically or as a consequence of chemotherapy/metabolic perturbation, renders cancer cells sensitive to EZH2 inhibition.…”
Section: Previous Studies Have Attempted To Exploit the Crosstalk Bet...mentioning
confidence: 99%